Contractual innovations: Memorandum of Understanding - López Fung, Jorge (2016)
This article addresses the most relevant aspects of Memorandum of Understanding, one of the most important contractual figures of our times. Through the article, the author explains this figure according to doctrinaire and jurisprudential pronouncements and determines its legal nature and the treatment the Peruvian legal system should grant to it.